An empirical test of Meyer and Allen's three-component model of organizational commitment in a Croatian context - Maslić Seršić, Darja (Array, 1999)
The study deals with evaluation of Meyer and Allen's three-component conceptualization of organizational commitment in Croatian society. The dimensionality of Meyer et al's (1993) scales, and their relationships with turnover intentions were examined. Participants were 766 professionals from 21 industrial organizations. Self-report questionnaire measures of job involvement, job satisfaction, and demographic data were also collected. Objective profit data were used as a measure of organizational efficiency. A significant contribution of organizational commitment in predicting turnover intention was found. However, the results speak in behalf of two- rather then three-dimensional definition of this construct. Employees from organizations which were identified as relatively successful according to objective profit data were higher committed to the organizations, had higher job satisfaction and lower turnover intentions in comparison to the employees from unsuccessful organizations.